The Size of Czech Agricultural Enterprises: Implications for Economic Efficiency - Redlichová, Radka; Tamáš, Vojtěch; Somerlíková, Kristina; Hlavackova, Jana (Česká zemědělská univerzita v Praze, 2025)
This study analyses the economic efficiency and size structure of agricultural enterprises in the Czech Republic, focusing on differences between organic and conventional farming systems during the 2016-2022 period. Key objectives include evaluating farm size distribution, profitability, and efficiency under varying conditions. Results reveal that organic farms are generally smaller and more reliant on subsidies, achieving lower production per hectare compared to conventional farms. However, their profit becomes comparable when subsidies are included. Conversely, conventional farms demonstrate greater efficiency, particularly among larger enterprises. These insights are pivotal for shaping agricultural policy with respect to production efficiency and food self-sufficiency.
Keywords: Farm structure; farm size; farm results; profitability; organic agriculture